Macroeconomic Adjustment in Developing Countries. (IMF Working Papers; Working Paper ;, 1988)
The paper deals with the two parts of the short-run adjustment problem in developing countries: the improvement of the current account and the reduction of inflation, the main cause in both cases being usually a fiscal deficit. It is shown how the two parts are related. Distinctions are made between the primary adjustment cost, which is inevitable, and the secondary cost which results, for example, from failure to devalue or from real wage rigidity. A sectoral cost benefit analysis is suggested. Reducing inflation involves both an inflation tax replacement and a price adjustment problem, and 'heterodox' policies designed to deal with the latter are analyzed.